Selective Hydrogenation of Biomass-derived Furfural over Supported Ni3Sn2 Alloy: Role of Supports - Rodiansono Rodiansono; Maria Dewi Astuti; Syahrul Khairi; Shogo Shimazu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
A highly active and selective hydrogenation of biomass-derived furfural into furfuryl alcohol was achieved using supported single phase Ni3Sn2 alloy catalysts. Various supports such as active carbon (AC), g-Al2O3, Al(OH)3, ZnO, TiO2, ZrO2, MgO, Li-TN, and SiO2 have been employed in order to understand the role of the support on the formation of Ni3Sn2 alloy phase and its catalytic performance. Supported Ni3Sn2 alloy catalysts were synthesised via a simple hydrothermal treatment of the mixture of aqueous solution of nickel chloride hexahydrate and ethanol solution of tin(II) chloride dihydrate in presence of ethylene glycol at 423 K for 24 h followed by H2 treatment at 673 K for 1.5 h, then characterised by using ICP-AES, XRD, H2- and N2-adsorption. XRD profiles of samples showed that the Ni3Sn2 alloy phases are readily formed during hydrothermal processes and become clearly observed at 2θ = 43-44o after H2 treatment. The presence of Ni3Sn2 alloy species that dispersed on the supports is believed to play a key role in highly active and selective hydrogenation of biomass-derived furfural towards furfuryl alcohol. Ni3Sn2 on TiO2 and ZnO supports exhibited much lower reaction temperature to achieved >99% yield of furfuryl alcohol product compared with other supports. The effects of loading amount of Ni-Sn, reaction conditions (temperature and time profile) on the activity and selectivity towards the desired product are systematically discussed.